Ethical Leadership Principles in South African Public Administration Lost Opportunity or Alive with Possibility - Naidoo, Goonasagree (Richtmann Publishing, 2012)
South Africa is a society emerging from a chequered and troubled past with a legacy ofimpairments in terms of education skills, opportunities, resentments, equality andperceptions. As in many societies, corruption is recognized as a major hindrance to goodgovernance in the public sector. The South African government has prompted the publicsector to focus on anti-corruption measures as part of their mechanisms to prevent andcurb corruption. It is evident that these mechanisms are insufficient to prevent and curbcorruption, due to poor governance practices, such as weakness and gaps in legislation.Furthermore, the public sector has seen that there are unethical and even toxic leaders,who exploit the loopholes in the systems and processes and seek to fulfil their personaldesires at the expense of their departments. It is therefore argued that there is increasinglya need for ethical leadership in the public sector. This article therefore suggests the need forethical leadership to prevent and curb corruption and to promote good governance in theS.A. public sector. Ethical leadership is associated with leader effectiveness and goodgovernance. Leaders need to demonstrate ethical leadership in their daily behaviors,decisions and actions. By sending out strong messages about ethics and establishing clearreward and sanction systems to hold public sector employees accountable for their actions,leaders can do a lot to promote good governance in the public sector. This may need to belinked to values inherent in certain uniquely cultural and South African traditions.